Evaluasi Non Performing Loan (NPL) Pinjaman Qardhul Hasan (Studi Kasus di BNI Syariah Cabang Yogyakarta) - Muhammad Akhyar Adnan; Firdaus Furywardhana (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2006)
The Qardhul-hasan is one of financing-product provided by Islamic banks. Unlike other financing products, the qardhul-hasan has some unique characteristics, including to entertaint a very specific customers who might be categorized as the dhuafa’ group. The study indicates that three of independent variables (customer’s basic characterisitic, reference, payment) are negatively correlated with dependent variable. However, the factor of purpose has no significant correlation. Further qualitative analysis also indicates that both bank management as well as qardhul hasan recepients have inappropriate perceptions toward the qardhul hasan product. In turn, it [the perception] worsens the NPL of Qardhul-hasan. Keywords: qardhulhasan, NPL, factors, evaluation.